Functional testing in human performance - Reimann, M. P.; Manske, R. C. (Human Kinetics, 2009)
This book offers clinicians the first-ever compilation of information on clinical and data-based functional testing for sport, exercise and occupational settings. This unique text serves as a primary resource for accurate assessment of individuals' functional abilities in order to develop programme prescriptions to enhance their performance. This new book is a comprehensive learning tool for novices and an essential reference for advanced clinicians. The text defines the role of function in physical performance and how it can be appropriately tested. The text also includes case studies that illustrate a variety of situations. Case studies include detailed statistical analysis and normative data, offering clinicians the opportunity to consider the application of functional testing and implementation strategies adaptable to their specific practice setting. Throughout the text, the functional tests are accompanied by photos for visual clarity. To enhance understanding, a companion DVD features live-action demonstrations of 40 of the most advanced tests. The DVD may be loaded onto a computer to offer convenient print-on-demand access to reproducible forms. By presenting the theory and detailing the practice, this text assists clinicians in understanding and incorporating functional testing to identify their patients' or clients' limitations, then enhancing their performance and rehabilitation.